ANALISA KUALITAS PELAYANAN KLINIK CENDEKIA HUSADA SIDOARJO DALAM MEMPERTAHANKAN LOYALITAS PASIEN REHABILITASI ADIKSI NAPZA - jurnalpps pps; Retno Dwi Hapsari; C. Sri Hartati; Gurendro Putro (Jurnal Manajerial Bisnis, 2018)
The purpose of this study was to find out and analyze the quality of services used to improve the qualityof services, to determine patient loyalty and actions taken by the Husada Sidoarjo Scholar Clinic inincreasing patient loyalty in the Husada Scholar Sidoarjo Clinic addiction. This research is a qualitativeresearch and involves data carried out by interview. Analytical data using interactive analysis models,the data will be analyzed in three stages, namely data reduction, data presentation and drawingconclusions. The results of the study showed that the quality of health services at the Scholar HusadaSidoarjo Clinic had run well, in terms of human resources, sufficient funds, and facilities andinfrastructure that had met the needs. Loyalty of rehabilitation patients of Sidoarjo Husada ScholarClinic patients is still lacking, this is because many patients are less disciplined, less active in theprogram, and less cooperative. Strategy Development of patient loyalty in Cendikia Husada SidoarjoClinic is done by good communication with patients, giving the impression of a friendly officer, andeasy service procedures.Keywords: service quality, strategy, patient loyalty.